Modulatory role of Spirulina platensis in oxidative stress, apoptosis, and gene expression in a rat model of dexamethasone-induced hepatotoxicity - Zedan, Amina; El-Moslemany, Amira M.; Bahnasy, Rasha M.; Eldamaty, Hanan Salah Eldeen; Ibraheim, Suzan S.; Alotaibi, Badriyah S.; Abdelmegeid, Mohamed; Shukry, Mustafa; Elolimy, Ahmed A. (Frontiers in Pharmacology, 2025)
The rising prevalence of hyperlipidemia and hepatic disorders has intensified interest in the therapeutic use of functional foods and botanical drugs. Spirulina platensis, a blue-green microalga, is known for its antioxidant, anti-inflammatory, and lipid-lowering properties. However, its potential hepatoprotective effects, particularly against glucocorticoid-induced liver damage, remain underexplored. This study aimed to investigate the protective effects of Spirulina platensis aqueous extract (SPAE) against dexamethasone (DEX)-induced oxidative stress, lipid dysregulation, apoptosis, hepatic injury, and associated gene expression changes in male rats. Forty male albino rats (150 ± 10 g) were randomly divided into four groups (n = 10). The control group received a standard diet and saline for 28 days. The second group was intraperitoneally injected with DEX (10 mg/kg) on alternate days for 28 days to induce hepatic and oxidative damage. The third and fourth groups were co-administered DEX with SPAE at 400 mg/kg and 800 mg/kg body weight/day orally for the same period. At the end of the experiment, key physiological and biochemical parameters were assessed, including feed intake, body weight gain, feed efficiency ratio (FER), and liver weight. Blood lipid profiles, liver enzymes (ALT, AST, ALP), total and direct bilirubin, and serum protein levels were analyzed. Additionally, antioxidant enzyme activities (SOD, CAT), markers of lipid peroxidation (MDA, NO), and mRNA expression levels of genes related to oxidative stress (Nrf2, SOD2), apoptosis (Bax, Bcl-2), lipid metabolism (PPAR-α), and DNA damage (p53) were evaluated using quantitative RT-PCR. SPAE treatment also modulated upstream regulators Keap1 and AMPK, supporting activation of the Nrf2 and PPAR-α pathways. The results revealed that SPAE significantly ameliorated DEX-induced hyperlipidemia, hepatic dysfunction, oxidative stress, and abnormal gene expression profiles, with the 800 mg/kg dose showing superior efficacy. These findings suggest that Spirulina platensis aqueous extract offers a promising protective effect against glucocorticoid-induced metabolic and hepatic disturbances, potentially through its antioxidant, anti-apoptotic, and gene-regulatory properties.